2023
DOI: 10.1021/acs.est.3c00835
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transformation of Micropollutants in Saline Wastewater by Peracetic Acid: The Overlooked Brominating Agents

Abstract: Peracetic acid (PAA) is an emerging alternative disinfectant for saline waters; HOBr or HOCl is known as the sole species contributing to halogenation reactions during PAA oxidation and disinfection. However, new results herein strongly indicated that the brominating agents (e.g., BrCl, Br 2 , BrOCl, and Br 2 O) are generated at concentrations typically lower than HOCl and HOBr but played significant roles in micropollutants transformation. The presence of Cl − and Br − at environmentally relevant levels could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Consequently, our measured [HOX] tot , if present primarily as HOBr, overpredicts the observed degradation rate of para -hydroxybenzoate, possibly due to an overestimation of the bimolecular rate constant between para -hydroxybenzoate and HOBr (Table S4). Recently, reactions with organic compounds involving previously overlooked species (e.g., Br 2 O, Br 2 ) have been found to contribute to rate constants for reactions attributed to HOBr being overestimated by similar orders of magnitude. , While re-evaluation of this bimolecular rate constant is beyond the scope of this work, our analysis with currently available values suggests that hypohalous acids are present at sufficient concentrations, if not in excess, to account for the observed rate of para -hydroxybenzoate degradation.…”
Section: Resultsmentioning
confidence: 70%
“…Consequently, our measured [HOX] tot , if present primarily as HOBr, overpredicts the observed degradation rate of para -hydroxybenzoate, possibly due to an overestimation of the bimolecular rate constant between para -hydroxybenzoate and HOBr (Table S4). Recently, reactions with organic compounds involving previously overlooked species (e.g., Br 2 O, Br 2 ) have been found to contribute to rate constants for reactions attributed to HOBr being overestimated by similar orders of magnitude. , While re-evaluation of this bimolecular rate constant is beyond the scope of this work, our analysis with currently available values suggests that hypohalous acids are present at sufficient concentrations, if not in excess, to account for the observed rate of para -hydroxybenzoate degradation.…”
Section: Resultsmentioning
confidence: 70%
“…10,21 However, our research indicated that these species should play an insignificant role in the electrochemical oxidation process. HOBr, predicted to be the most abundant bromine species 19,55 and highly reactive with phenolic compounds, 56 was identified as the main contributor if free bromines were involved in phenol oxidation. Other bromine species like BrCl and BrOCl were not considered due to their rapid transformation into HOBr.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other bromine species like BrCl and BrOCl were not considered due to their rapid transformation into HOBr. 19 It is evident from Figure 2b that k' BPA (0.031 min −1 ) was only slightly higher than k' IBU (0.021 min −1 ), but k HOBr,BPA (9.4 × 10 4 M −1 s −1 ) exceeded k HOBr,IBU (0.39 M −1 s −1 ) by 5 orders of magnitude, 22 reflecting that HOBr was not the predominant reactive species in the Br − -involved electrochemical system. In addition, the small difference in k' BPA values obtained in the absence or presence of Br − suggests that free halogens may not be crucial contributors to the reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, PAA alone could only directly degrade certain organic contaminants with electron-rich structures (e.g., sulfur moiety, aromatic ring, and CC bond) . Up to now, a number of activation strategies have been proposed to enhance the oxidative performance of PAA, such as energy input (e.g., ultraviolet, , heat, electrochemistry, microwave, and ultrasound), metal catalysts (e.g., homogeneous and heterogeneous transition metals), carbon materials, , and anionic catalysts (e.g., phosphate, bromide, , iodine, , chloride, and nitrite), etc.…”
Section: Introductionmentioning
confidence: 99%